8x-(5x+4)=7+(2x-3)

Simple and best practice solution for 8x-(5x+4)=7+(2x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-(5x+4)=7+(2x-3) equation:


Simplifying
8x + -1(5x + 4) = 7 + (2x + -3)

Reorder the terms:
8x + -1(4 + 5x) = 7 + (2x + -3)
8x + (4 * -1 + 5x * -1) = 7 + (2x + -3)
8x + (-4 + -5x) = 7 + (2x + -3)

Reorder the terms:
-4 + 8x + -5x = 7 + (2x + -3)

Combine like terms: 8x + -5x = 3x
-4 + 3x = 7 + (2x + -3)

Reorder the terms:
-4 + 3x = 7 + (-3 + 2x)

Remove parenthesis around (-3 + 2x)
-4 + 3x = 7 + -3 + 2x

Combine like terms: 7 + -3 = 4
-4 + 3x = 4 + 2x

Solving
-4 + 3x = 4 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-4 + 3x + -2x = 4 + 2x + -2x

Combine like terms: 3x + -2x = 1x
-4 + 1x = 4 + 2x + -2x

Combine like terms: 2x + -2x = 0
-4 + 1x = 4 + 0
-4 + 1x = 4

Add '4' to each side of the equation.
-4 + 4 + 1x = 4 + 4

Combine like terms: -4 + 4 = 0
0 + 1x = 4 + 4
1x = 4 + 4

Combine like terms: 4 + 4 = 8
1x = 8

Divide each side by '1'.
x = 8

Simplifying
x = 8

See similar equations:

| -5x+4(-3+3)=-192 | | x^2*y-3*x*y=0 | | 5(2a+4)=6a-4 | | 1.2m=.6 | | (x^2-5x-3)(x^2-5x-5)=3 | | -x+6x-9=0 | | 2y=-10x+4 | | -7=9x+16-10 | | 2(x+p)=3(6p-x) | | 9k-3k=30 | | 3y+4=y+18 | | -44-1x=28-4x | | x-7.1=-6.2 | | -(3y+1)-(-2y-7)=2 | | 96-2x=43x+16 | | 7(7x-3)+10x= | | 2x+80=158 | | 5p-3=32 | | 3x=3x+2 | | x=.4+(-.2y) | | B-2+6B=27 | | 3x/4=6 | | 6x-11x+4=0 | | 13x^2+1-[7(x^2-8)+5]= | | 6x^7-18x^4+24x^6= | | 6+2y-2=9y+13-6y | | 14(t-3)+4t=6(3t+3)-10 | | 2x-5=x+7+2x | | 5fg+g^2=0 | | 2x+-.5=-.75 | | 5fg+g^2=03 | | 7x+15=29 |

Equations solver categories